HUBUNGAN HARGA DIRI DENGAN KOMUNIKASI INTERPERSONAL GURU PAUD SE-KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Rika Hestia Marlisa; Rita Kurnia; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to know the level and relationship between self esteem and interpersonal communication of PAUD teachers in Tempuling Subdistrict of Indragiri Hilir Regency. The samples in this research were PAUD teachers in Tempuling Subdistrict of Indragiri Hilir Regency which amounted to 52 teachers. The method used is Person Product Moment correlation to see the relationship between self esteem variable and interpersonal communication. Data collection techniques used were questionnaires in the form of a Likert scale. Data analysis techniques use scale trials and statistical method analysis. From the results of the study, the level of self-esteem of teachers is in the high category with a percentage value of 79.62% and the level of interpersonal communication of teachers is in the high category with a percentage value of 82.19%. Based on the results of hypothesis testing obtained there is a positive and significant relationship between self-esteem and interpersonal communication of PAUD teachers throughout Tempuling District, Indragiri Hilir Regency. This can be seen from the correlation coefficient value of rxy = 0.383 and the determinant coefficient value generated is KD = r2 x 100% = 14.7%, meaning that self-esteem has an influence of 14.7% on interpersonal communication.Key Words: Self esteem, Interpersonal communication